شخصية البطل من خلال ظاهرة التنغيم في رواية "أرني أنظر إليك" لخولة حمدي - جمانة دلال; رقية عمار (University of Eloued جامعة الوادي, 2025)
الملخص: تسعى هذه الدراسة إلى تسليط الضوء على ظاهرة التنغيم بوصفها بُعدًا صوتيًّا ووظيفيًّا له أثر كبير في الخطاب، ولا سيما في الكشف عن الأبعاد النفسية والانفعالية للشخصية المتكلمة. وقد تم اعتماد موازين التنغيم التي وضعها الدكتور تمام حسان، نظرًا لمنهجيته الواضحة ورؤيته الوظيفية التي تربط الصوت بالمعنى.واعتمدنا في الجانب التطبيقي على رواية "أرني أنظر إليك" لما تحمله من حمولة نفسية ولغوية عميقة، تعبّر عن صراعات داخلية وتجليات وجدانية انعكست في الخطاب الروائي. وقد تم تحليل خطابات البطل وفق الموازين: الإيجابي، النسبي، السلبي، صعودًا وهبوطًا، بهدف الوقوف على العلاقة بين التنغيم والتحول النفسي في الشخصية. قد خلصت هذه الدراسة إلى مجموعة من النتائج المهمة، لعلّ أبرزها: • تبيّن أن التنغيم يُعد أداة دقيقة وفعالة في كشف نفسية المتكلم وهويته، من خلال تتبع نبرة الحديث وتغيّرها، وهو ما أثبتته الدراسة التطبيقية في الرواية المدروسة. • أظهرت الدراسة أن موازين التنغيم – كما صاغها تمام حسان – تعكس بُعدين متلازمين: بُعدًا فيزيولوجيًّا وآخر نفسيًّا، مما يؤكد العلاقة الوثيقة بين الصوت والانفعال، ويُبرز مدى تأثير الحالة النفسية في تشكيل الخطاب. • كشفت نتائج الإحصاء تفاوتًا في النسب المئوية للأنماط التنغيمية، مما يعكس تنوعًا في السمات النفسية والانفعالية لشخصية البطل، ويدل على تعدّد مستويات التوتر والصراع الداخلي لديه. • تُعد شخصية البطل "مالك" – بحسب تصنيفات الدراسات النفسية الحديثة – من الشخصيات المضطربة في بنيتها النفسية، وهو ما تعززه أنماط التنغيم المختلفة التي وردت في خطابه الداخلي. • دعمت نتائج الدراسة ما أشار إليه الرازي، في ربطه بين الأحوال النفسية والتغيرات الصوتية والعضوية، مما يمنح التنغيم بُعدًا تحليليًّا مهمًا في فهم الخطاب المكتوب والمُتلفظ. Résumé : فرنسية أو انجلزية This study seeks to shed light on the phenomenon of intonation as a phonetic and functional dimension that plays a significant role in discourse, particularly in revealing the psychological and emotional dimensions of the speaking character. The study adopts the intonation scales developed by Dr. Tammam Hassan, due to his clear methodology and functional perspective that links sound to meaning. For the practical part, the novel “Arni Anzur Ilayk” (Let Me Look at You) was chosen, given its rich psychological and linguistic content that reflects deep internal conflicts and emotional expressions throughout the narrative discourse. The protagonist’s dialogues were analyzed according to the intonation scales: positive, relative, and negative—both rising and falling—to explore the relationship between intonation and psychological transformation in the character. The study reached several important findings, most notably: • Intonation proves to be a precise and effective tool for revealing the speaker’s psychology and identity through tracking tonal shifts, as confirmed by the applied analysis of the novel. • The study showed that Tammam Hassan’s intonation scales reflect two interrelated dimensions: a physiological and a psychological one, affirming the strong connection between voice and emotion, and highlighting the influence of mental states in shaping discourse. • Statistical results indicated noticeable variation in the frequency of intonation patterns, reflecting the psychological and emotional diversity of the protagonist and multiple levels of tension and internal conflict. • The character “Malik” is classified—according to modern psychological studies—as a psychologically disturbed figure, as supported by the various intonation patterns found in his inner speech. • The findings also align with early scholars like Al-Razi, who linked psychological states to vocal and physiological changes, thus emphasizing the analytical value of intonation in understanding both written and spoken discourse.
مذكرة .ماستر . لسانيات عامة. 2025